Trigeminal neuralgia: An insight into the current treatment modalities - Silky Rajesh Punyani; Vishal Ramesh Jasuja (Elsevier, 2012)
Trigeminal neuralgia (TN) is one of the most excruciating pain syndromes afflicting the orofacial region. Trigeminal neuralgia may be primary i.e. idiopathic or secondary, resulting from trauma or a CNS lesion. Considering the agonizing nature of the disease and TN being the commonest of the neural maladies affecting the orofacial region it is important for the oral physician to be aware of all available treatment options. This article makes an attempt to present a brief insight into the current treatment modalities that are on hand to treat this condition. From the perspective of the oral physician the pharmacotherapy constitutes the cornerstone in the management of TN. At the same time, it is also important to be aware and updated of the role of the oral surgeon and radiologist in the application of the array of interventional procedures available for treating TN.